Is Portuguese regional growth schumpeterian? An empirical assessment of the relation between schooling, firm destruction and firm productivity - Aurora Amélia Castro Teixeira; Pedro Cosme Vieira (European Regional Science Association (ERSA), 2004)
A study focusing Portuguese textile firms dynamics during the eighties and nineties (Teixeira, 2002; Teixeira and Vieira, 2004) demonstrated that plants which tended to hire workers with higher levels of human capital (education) were those that, on average, presented a lower probability of survival. Macro-level evidence on the relation between human capital, per capita income and productivity seems to be at odds with the micro evidence reported. Specifically, at the economy level the bulk of studies found a positive relation between human capital accumulation and productivity dynamics (Michie et al, 2002; Teixeira and Fortuna, 2003; Maudos et al, 2003) which, at first glance, seems hard to match with the micro-level evidence suggesting that the accumulation of human capital is associated with higher failure rates on firm's behalf. The potential explanation for this may be related with the fact that firms can be positioned into one of the two possible states – low productivity and low risk or high productivity and high risk. In order for a low productivity-low risk firm to become high productivity-high risk firm it has to hire top educated workers. Successful high productivity-high risk firms, i.e, those that survive, are the `engine of growth'. This may explain that regions, which have higher levels of human capital, be those that, in the medium term, have higher levels of per capita income and higher firm failure rates. This association of higher per capita income/productivity levels and higher firm destruction rates translates the schumpeterian issue of creative destruction (Schumpeter, 1942). In the present paper we try to validate this theoretical explanation using empirical evidence at the regional level. Based on panel data relative to 27 Portuguese regions (NUTIII) over the period 1992-1999, we estimate an econometric model of the relation between human capital, firm productivity and firm failure rates. Estimation results suggest important policy implications, namely that policy measures involving schooling incentives, i.e., human capital supply side focused policies, should be replaced by more human capital demand side focused policies aiming to easy bankruptcy processes. Keywords: Schooling, Productivity, Firm Survival, Regions
Keywords: 330; Schooling; Productivity; Firm Survival; Regions